STRUKTUR DAN FUNGSI SOSIAL UNGKAPAN LARANGAN MASA BAYI DAN KANAK-KANAK DI KENAGARIAN BATU BULEK KECAMATAN LINTAU BUO UTARA KABUPATEN TANAH DATAR - Juwita, Resi; Hasanuddin WS, Hasanuddin WS; Juita, Novia (Jurnal Bahasa dan Sastra, 2014)
The purpose of this study is to describe the structure and function of social expressions of prohibition of infancy and childhood in Kenagarian Batu Bulek Kecamatan Lintau Buo Utara Kabupaten Tanah Datar. Type this research is qualitative research with methods of descriptive. The object of the research was the oral literary expressions of prohibition of infancy and childhood are used communities in Kenagarian Batu Bulek Kecamatan Lintau Buo Utara Kabupaten Tanah Datar. This research comprises the informant and the informant's main one person supporting two people. The collection of research data is made through two stages, namely the stage of recording oral literary expression restrictions and environmental data collection stage of the narrative. Results of this study found as many as 68 expressions of prohibition of infancy and childhood. through two phases, namely the recording of oral literary stage expression restrictions and environmental data collection stage of the narrative. The ban on the phrase structure consists of two forms, that is composed of two parts that form of cause and effect, and the three-part structure of the sign, conversion, and the result. The social function of these prohibitions is the expression of the emotion of the religious belief or thicken, a collective imaginary projection system, educating, and bans.